Development of Supplementary Basic Physics Practicum Based on Problem-Solving Method Assisted with Augmented Reality (AR) Technology - Johan, Henny; Putri, Desy Hanisa; Risdianto, Eko; Johan, Septi; Sudirman, Sudirman; Widiasih, Widiasih (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2023)
Physics practicum is an important activity in basic physics courses that involve contextual physics concepts, such as cases in coastal areas which can demand students’ problem-solving skills. Covid-19 has caused basic physics practicum activities to become difficult to carry out in a laboratory scale, thus alternative solution is necessary to perform practical activities in the Covid-19 situation, namely by utilizing Augmented Reality (AR) technology. AR can help visualize physics concepts and practicum activity procedures relevant to practicum activities. This study aimed to develop an AR-assisted practicum guidebook product oriented toward a problem-solving method by presenting several cases of natural potential in local coastal areas. This study used an R&D method with a 4D model. However, this study was limited to the development stage. Data were collected with validation sheets and student response questionnaire sheets. These data were then analyzed with descriptive qualitative data analysis technique. Based on the data analysis results, many students had difficulties in carrying out physics practicum activities during the Covid-19 pandemic. This occurred due to the unaccessible practicum video procedures in the guidebook during the offline condition. Furthermore, the practicum procedure guidebook was only in narrative text, unable to stimulate high-level thinking skills by presenting coastal area cases. Students must be introduced deeper to the potential of coastal areas and their relation to physics concepts.